A cluster of cholera among patients in a Vietnamese district hospital in 2010 - Thuan Huu Vo; Ninh Hoang Le; J. Pekka Nuorti; Lan Trong Phan; Nguyen Nhu Tran Minh (Journal of Infection in Developing Countries)
On July 20, 2010, three cases of cholera were reported from a district hospital in Ca Mau province, Vietnam. We investigated the likely source and mode of transmission of the outbreak. All hospitals in the province were requested to notify cases of acute watery diarrhoea. Epidemiological, clinical, and laboratory data were collected. Between July 12 and 22, seven cases with positive culture for Vibrio cholera were identified. Six cases were epidemiologically linked to the index case. Basic infection control practices were not in place at the hospital. Clinicians and public health staff should consider the possibility of nosocomial cholera transmission even in non-endemic areas.